A highly sensitive and selective fluoride sensor based on a riboswitch-regulated transcription coupled with CRISPR-Cas13a tandem reaction. Issue 35 (9th August 2021) - Ma, Yuan; Mou, Quanbing; Yan, Peng; Yang, Zhenglin; Xiong, Ying; Yan, Deyue; Zhang, Chuan; Zhu, Xinyuan; Lu, Yi
Abstract : A fluoride sensor based on riboswitch-regulated transcription coupled with Cas13a sensor can detect fluoride in water with a portable fluorometer. This sensor expands nuclei acid sensors to an anion, with high sensitivity and selectivity against other common anions. Abstract : Nucleic acid sensors have realized much success in detecting positively charged and neutral molecules, but have rarely been applied for measuring negatively charged molecules, such as fluoride, even though an effective sensor is needed to promote dental health while preventing osteofluorosis and other diseases. To address this issue, we herein report a quantitative fluoride sensor with a portable fluorometer readout based on fluoride riboswitch-regulated transcription coupled with CRISPR-Cas13-based signal amplification. This tandem sensor utilizes the fluoride riboswitch to regulate in vitro transcription and generate full-length transcribed RNA that can be recognized by CRISPR-Cas13a, triggering the collateral cleavage of the fluorophore-quencher labeled RNA probe and generating a fluorescence signal output. This tandem sensor can quantitatively detect fluoride at ambient temperature in aqueous solution with high sensitivity (limit of detection (LOD) ≈ 1.7 μM), high selectivity against other common anions, a wide dynamic range (0–800 μM) and a short sample-to-answer time (30 min). This work expands the application of nucleic acid sensors to negatively charged targets and demonstrates their potential for the on-site and real-time detection of fluoride in environmental monitoring and point-of-care diagnostics.